Politics and participation: a project for peace with the early childhood (Quaestiones Disputatae: temas en debate, 2016)
This article gives evidence to the need of denature of the idea of subordination of the child in the presence of adults. The idea is to relocate the childhood notion in a place where the capacity of the child to create symbols and generate culture can be recognized. This is seen in his preparation to be a citizen through an education which recognizes, value and respects him. This would emancipate him in the common construction of the shared society with adults. This article also conceives a child as a subject with rights, with the capacity of taking part in issues that affect him. In this way, the idea of participation as right- dutie is developed in every scene to favor the formation of politics, the integral human development and the search of the common well for peace. This becomes the origin of politics and peace to understand them, and see their real sense to contribute to the construction of social fabric.
Keywords: childhood; participation; peace; politics